PENGARUH EARNING POWER, FIRM SIZE, DAN LEVERAGE TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK TAHUN 2011-2015 - Munawarah Munawarah (JURNAL MUTIARA AKUNTANSI, 2017)
The aim of this study is to examine and analyze the earnings power, firm siz, good corporate governance and leverage to the earnings management of the food and beverage’s sub sectors listed on the Indonesian Stock Exchange in the period 2011-2015. The research was causal research method and used secondary data. The population was 14 companies, and 60 of them were used as the samples, which taken by purposive sampling technique. The data were analyzed by using multiple linear regression analysis. The result of the research showed that simultaneously earnings power, firm size, and leverage had significant effect to earnings management. Partially, earnings power and firm size had no significant effect to earnings management. While, leverage had a positif significant effect to earnings management. The R2 was 0,149, which means that 14,9 % variation of earnings management variable can be explained by variations of earning power, firms size and leverage. While the remaining 85,1 % was affected by other factors.Keyword : Earnings Power, Firm Size, , Leverage, and Earnings Management